A Critical Analysis of Predominant Colours in the Movie Pudhupettai - Mouly, Chandra V; Nandhini, C (International Journal of Computer Sciences and Engineering, 2018)
This research papera aimed to anylse the predominant colors like red, blue, and green used in the newly released movie named ‘Pudhupettai’. Also, this research examines the use of red and green colour lightings in the movie Pudhupettai to expose the scene mood and the character’ state of mind with reference to colour psychology in movies. Colour has always been one of the nonverbal languages in communication. Story telling has been followed around the world for ages in various forms including the traditional and new media. Films have paved a massive way among the audience to attain exposure in various platforms. The aim of the directors in general would be making the scene clearer and more realistic to watch and to attract numerous viewers on the stand. Hence, this explores the possibilities of such used emotions using the colours and the pattern of character discourse according to the state of mind. Green again is used in both negative and positive terms to depict the character’s start of mind. Green is unique in the sense that it is the quintessential colour of nature, yet green light can also make a place look eerie or portray illness. Human mood is set upon several ranges and on several platforms. In here, movie serves as a platform to depict a mood or emotion through Red and Green Light. The behavioural understanding of characters is understood through the colour revolving around them. The study about the application for colour psychology is new a very area to explore in the Indian context. This research results can be extended to other films and other forms of communication.